MFI type molecular sieve catalyst as well as preparation method and application thereof
By developing an MFI-type molecular sieve catalyst with a sheet-like structure and a specific pore structure, the existing ZSM-5 molecular sieve catalyst has poor catalytic performance and short service life in the MTP process, and the improvement of propylene yield and prolonging catalysts are achieved. Lifespan effect.
Patent Information
- Application Number
- CN202411544795.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-31
- Publication Date
- 2025-02-11
AI Technical Summary
The existing ZSM-5 molecular sieve catalysts have poor catalytic performance, poor carbon deposit and powder resistance, and short service life in the MTP process, resulting in low propylene yield.
An MFI type molecular sieve catalyst is provided, which is a sheet-shaped structure, has a straight cylinder type and a Z-shaped channel structure. By regulating the thickness of the sheet-shaped structure, the length of the straight cylinder type channel is adjusted, and catalytic activity and anti-carbon accumulation performance are improved.
The catalytic activity of the catalyst is improved, the occurrence of side reactions is inhibited, the yield of propylene is improved, and the service life of the catalyst is extended.
Smart Images

Figure CN119406445A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of catalyst preparation, and in particular to an MFI type molecular sieve catalyst, a preparation method and application thereof. Background Art
[0002] As an important basic raw material in the petrochemical industry, propylene is mainly used to produce downstream products such as polypropylene (PP), acrylic acid (AA), butanol (BA), acetone (PK), phenol (Phenol), octanol (CA), acrylonitrile (AN), propylene oxide (PO) and isopropyl alcohol (IPA). In recent years, coal chemical and propane dehydrogenation (PDH) devices have been gradually industrialized. The methanol to olefins (MTO) process and the methanol to propylene (MTP) process are important ways to obtain propylene products in the coal chemical route. At present, both technologies have been industrialized. The target products of the MTO technology are mainly ethylene and propylene in equal proportions, while the target products of the MTP technology are mainly propylene.
[0003] MFI molecular sieves play an important role in the MTP process. Among them, ZSM-5 molecular sieves, as one of the MFI molecular sieves, are the preferred catalysts for the MTP process. Small-grained ZSM-5 molecular sieves (grains less than 100nm) and multi-level pore ZSM-5 molecular sieves have a large number of mesopores and micropores and a large specific surface area, which can effectively shorten the diffusion path of the reactants and accelerate the reaction process. However, in actual application, there is a lot of carbon deposits inside the catalyst. During charcoal burning and regeneration, it is easy to cause local overtemperature, which leads to the destruction of the catalyst structure and the occurrence of pulverization. In addition, small-grained ZSM-5 molecular sieves are difficult to filter and wash during the production process due to their small grains, which not only easily causes the loss of catalysts, but also increases the amount of wastewater, resulting in high production costs. The microporous channels in traditional ZSM-5 molecular sieves limit the mass transfer and diffusion of reactants and products between active centers, especially when macromolecules participate in the reaction, which is easy to cause side reactions, a lot of carbon deposits inside the catalyst, and catalyst deactivation. In addition to the above problems, the existing ZSM-5 molecular sieve catalyst also has problems such as low yield and short service life during the production process.
[0004] In summary, researching and developing an MFI type molecular sieve catalyst with high catalytic activity, good resistance to carbon deposition, strong resistance to pulverization, and long single cycle and overall operating life is of great significance for improving the yield of propylene produced by the MTP process. Summary of the invention
[0005] The main purpose of the present invention is to provide an MFI type molecular sieve catalyst, a preparation method and application thereof, so as to solve the problem that the ZSM-5 molecular sieve in the prior art has poor catalytic performance, poor resistance to carbon deposition and pulverization, and short service life, thereby resulting in a low yield of propylene obtained by the MTP process.
[0006] In order to achieve the above-mentioned purpose, the first aspect of the present invention provides an MFI type molecular sieve catalyst, which is a sheet structure, has a straight cylindrical channel structure in the thickness direction, and has a Z-shaped channel structure in the plane direction; the cross-sectional shape of the straight cylindrical channel is elliptical, the length of its major axis is 0.57~0.58nm, and the length of its minor axis is 0.51~0.52nm; the thickness of the MFI type molecular sieve catalyst is 90~200nm.
[0007] Furthermore, the plane of the MFI molecular sieve catalyst includes mutually perpendicular x-direction and y-direction, the maximum value along the x-direction is 200-400nm, and the maximum value along the y-direction is 400-700nm; preferably, in the MFI molecular sieve catalyst, the shape of the cross section perpendicular to the thickness direction is a hexagon, the hexagon includes two parallel sides, and the direction of the side is the y-direction, preferably the vertical distance between the two is 200-400nm, and preferably the ratio of the maximum value along the y-direction to the length of the side is (1.4-2.3):1.
[0008] Furthermore, the pore volume of the MFI molecular sieve catalyst is 0.17 to 0.23 cm 3 / g, with a specific surface area of 330-375cm 2 / g.
[0009] The second aspect of the present application also provides a method for preparing the above-mentioned MFI type molecular sieve catalyst provided by the present application, and the preparation method comprises: step S1, performing a first crystallization treatment on a first silicon source, a first template, a base and a first solvent to obtain a system containing seed crystals; step S2, performing a second crystallization treatment on a second silicon source, an aluminum source, a second template, a directing agent, a second solvent and seed crystals to obtain a system containing a crystallized product; the molar ratio of the second template to the directing agent is (0.2 to 0.5): (0.1 to 0.8); step S3, calcining the crystallized product to obtain an MFI type molecular sieve catalyst.
[0010] Further, step S1 includes: a first mixing of a first silicon source and a first template to obtain a first mixed solution; dissolving an alkali in a first solvent and then mixing the alkali with the first mixed solution for a second time to obtain a second mixed solution; performing a first crystallization treatment on the second mixed solution to obtain a seed-containing system; preferably, the molar ratio of the first silicon source to the first template is (1-1.1):(0.08-0.3); preferably, the weight ratio of the alkali to the first solvent is (0.1-0.3):(15-20); preferably, the weight ratio of the first solvent to the first mixed solution is (15-20):(0.5-3); preferably, stirring is performed during the first mixing and the second mixing, preferably the stirring rate of the first mixing is 100-150 rpm, the time is 20-30 min, and the stirring rate of the second mixing is 250-300 rpm, the time is 60-180 min.
[0011] Further, step S2 includes: mixing the second silicon source and the second template for a third time to obtain a third mixed liquid; mixing the third mixed liquid with the aluminum source, the guiding agent, the second solvent and the seed crystal for a fourth time to obtain a fourth mixed liquid, and performing a second crystallization treatment on the fourth mixed liquid to obtain a crystallized product system; preferably, the molar ratio of the second silicon source to the aluminum source is (0.8-1.2):(0.001-0.002); preferably, the molar ratio of the second silicon source to the second template is (0.9-1.1):(0.25-0.4); preferably, the weight percentage of the seed crystal in the fourth mixed liquid is 2-8wt%; preferably, stirring is performed during the third mixing and the fourth mixing, preferably the stirring rate of the third mixing is 400-450rpm, the time is 30-100min, and the stirring rate of the fourth mixing is 300-400rpm, and the time is 20-30min.
[0012] Furthermore, the first crystallization treatment includes a first temperature rise stage and a first constant temperature stage in sequence, wherein the temperature rise rate of the first temperature rise stage is 2-10° C. / h, the temperature of the first constant temperature stage is 95-105° C., and the time is 72-82 hours.
[0013] Furthermore, the second crystallization treatment includes a second temperature rise stage and a second constant temperature stage in sequence, wherein the temperature rise rate of the second temperature rise stage is 2-5°C / h, the temperature of the second constant temperature stage is 150-185°C, and the time is 40-60h.
[0014] Further, the first silicon source and the second silicon source are each independently selected from one or more of the group consisting of tetraethyl orthosilicate, silica sol, water glass, silica gel and white carbon black; preferably, the first template and the second template are each independently selected from one or more of the group consisting of tetrapropylammonium hydroxide, tetrapropylammonium bromide, n-butylamine and triethylamine; preferably, the aluminum source is selected from one or more of the group consisting of aluminum nitrate, aluminum sulfate, sodium aluminate and pseudo-boehmite; preferably, the directing agent is selected from one or more of the group consisting of hexadecyltrimethylammonium bromide, urea, ethylamine and ammonium nitrate; preferably, the directing agent is a combination of ethylamine and urea, and the molar ratio of ethylamine to urea is (0.02-1):(0.12-2); preferably, the base is selected from one or more of the group consisting of ethylamine, sodium hydroxide, sodium carbonate, potassium hydroxide and sodium bicarbonate; preferably, the first solvent and the second solvent are each independently selected from one or more of the group consisting of water, ethanol and methanol.
[0015] Furthermore, step S1 also includes: sequentially performing a first solid-liquid separation and a first drying on the system containing the seed crystals to obtain the seed crystals; preferably, the temperature of the first drying is 60 to 140°C, and the time is 8 to 24 hours; preferably, in step S3, the calcination temperature is 400 to 600°C, and the time is 4 to 10 hours; preferably, between step S2 and step S3, it also includes: sequentially performing a second solid-liquid separation and a second drying on the system containing the crystallized product, and more preferably the temperature of the second drying is 80 to 120°C, and the time is 4 to 10 hours.
[0016] The third aspect of the present application also provides an application of the above-mentioned MFI type molecular sieve catalyst provided in the present application in the methanol to propylene reaction.
[0017] The microporous channels of the traditional ZSM-5 molecular sieve limit the mass transfer and diffusion of reactants and products between active centers, which easily leads to problems such as catalyst pulverization, deactivation and the occurrence of side reactions. Applying the technical solution of the present invention, the MFI molecular sieve catalyst in the present application is a sheet structure, and can regulate the length of the straight-tube channel by regulating the thickness of the sheet structure under the premise of maintaining the overall grain morphology size of the molecular sieve, so that it can better adapt to the methanol to propylene (MTP) reaction. The thickness of the MFI molecular sieve catalyst and the cross-sectional shape and size of the straight-tube channel include but are not limited to the above ranges, and it is limited to the above ranges. On the one hand, the catalytic activity of the MFI molecular sieve catalyst can be improved, and the generated product can be rapidly diffused, thereby suppressing the occurrence of side reactions and improving the yield of the target product. On the other hand, the generation of carbon deposits can be effectively suppressed, and the generated carbon deposits are mostly covered at the orifice of the straight-tube channel, which is convenient for controlling the temperature of the charcoal burning regeneration process, suppressing the pulverization phenomenon caused by local overheating of the catalyst, thereby extending the service life of the MFI molecular sieve catalyst. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0019] Figure 1 The X-ray diffraction pattern (XRD pattern) of the MFI molecular sieve catalyst prepared in Example 1 of the present application is shown;
[0020] Figure 2 The scanning electron microscope image (SEM image) of the MFI type molecular sieve catalyst prepared in Example 1 of the present application is shown;
[0021] Figure 3 The scanning electron microscope image (SEM image) of the commercially available small-grain ZSM-5 molecular sieve catalyst in Comparative Example 1 of the present application is shown. DETAILED DESCRIPTION
[0022] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below in conjunction with the embodiments.
[0023] As described in the background technology, the existing ZSM-5 molecular sieve has poor catalytic performance, poor resistance to carbon deposition and pulverization, and short service life, which leads to the problem of low yield of propylene obtained by MTP process. In order to solve the above technical problems, the first aspect of the present application provides an MFI molecular sieve catalyst, which is a sheet structure, has a straight-cylindrical pore structure in the thickness direction, and has a Z-shaped pore structure in the plane direction; the cross-sectional shape of the straight-cylindrical pore is elliptical, the length of its major axis is 0.57-0.58nm, the length of its minor axis is 0.51-0.52nm, and the thickness of the MFI molecular sieve catalyst is 90-200nm.
[0024] Compared to traditional ZSM-5 molecular sieve, due to its microporous channel limiting the mass transfer and diffusion of reactants and products between active centers, it is easy to cause the problems such as catalyst pulverization, deactivation and the occurrence of side reactions. The MFI type molecular sieve catalyst in the present application is a sheet structure, and can be regulated by regulating the thickness of the sheet structure to regulate the length of the straight-tube channel under the premise of maintaining the overall grain morphology size of the molecular sieve, so that it is better adapted to methanol to propylene (MTP reaction). The thickness of the MFI type molecular sieve catalyst and the cross-sectional shape and size of the straight-tube channel include but are not limited to the above range, which is limited to the above range, on the one hand, the catalytic activity of the MFI type molecular sieve catalyst can be improved, the product generated can be rapidly diffused, thereby suppressing the occurrence of side reactions, improving the yield of the target product, on the other hand, the generation of carbon deposits can be effectively suppressed, and the carbon deposits generated are mostly covered at the orifice of the straight-tube channel, which is convenient to control the temperature of the charcoal burning regeneration process, suppressing the pulverization phenomenon caused by local overheating of the catalyst, thereby extending the service life of the MFI type molecular sieve catalyst.
[0025] In a preferred embodiment, the plane of the MFI molecular sieve catalyst includes mutually perpendicular x-direction and y-direction, the maximum value along the x-direction is 200-400nm, and the maximum value along the y-direction is 400-700nm. The maximum value along the x-direction and the maximum value along the y-direction include but are not limited to the above ranges, and limiting them within the above ranges is conducive to maintaining the grain size of the MFI molecular sieve catalyst within a suitable range, thereby facilitating filtering and washing thereof, and is conducive to improving the recovery rate of the catalyst, thereby reducing the loss of the catalyst.
[0026] In order to further regulate the grain size of the MFI molecular sieve catalyst within an appropriate range, it is more convenient to filter and wash it, thereby further improving the recovery rate of the catalyst and reducing the loss of the catalyst, preferably, in the MFI molecular sieve catalyst, the shape of the cross section perpendicular to the thickness direction is a hexagon, and the hexagon includes two parallel sides, and the direction of the side is the y direction, and the vertical distance between the two is preferably 200 to 400 nm, and the ratio of the maximum value along the y direction to the length of the side is preferably (1.4 to 2.3):1.
[0027] In a preferred embodiment, the pore volume of the MFI molecular sieve catalyst is 0.17 to 0.23 cm 3 / g, with a specific surface area of 330-375cm 2 / g. The pore volume and specific surface area of the MFI molecular sieve catalyst include but are not limited to the above ranges. Limiting them within the above ranges is conducive to improving the catalytic activity of the MFI molecular sieve catalyst, and is conducive to improving the mass transfer and diffusion efficiency between the reactants and products in the active centers of the catalyst, thereby helping to inhibit the occurrence of side reactions, and helping to improve the yield of the target product. It is also conducive to inhibiting the formation of carbon deposits inside the MFI molecular sieve catalyst, and is conducive to making the temperature of various parts of the catalyst more uniform during the charcoal burning regeneration process, thereby helping to improve the catalyst's ability to resist carbon deposition and anti-pulverization, and further helping to extend its service life.
[0028] The second aspect of the present application also provides a method for preparing the above-mentioned MFI type molecular sieve catalyst provided by the present application, and the preparation method comprises: step S1, performing a first crystallization treatment on a first silicon source, a first template, a base and a first solvent to obtain a system containing seed crystals; step S2, performing a second crystallization treatment on a second silicon source, an aluminum source, a second template, a directing agent, a second solvent and seed crystals to obtain a system containing a crystallized product; the molar ratio of the second template to the directing agent is (0.2 to 0.5): (0.1 to 0.8); step S3, calcining the crystallized product to obtain an MFI type molecular sieve catalyst.
[0029] In the present application, a seed crystal is first prepared through step S1 to facilitate the growth of a crystallized product in step S2; in step S2, the seed crystal is subjected to a second crystallization treatment with a second silicon source, an aluminum source, a second template, a directing agent, and a second solvent, which can regulate the crystal growth direction, thereby improving the crystallization efficiency of the second crystallization treatment and obtaining a crystallized product of a specific crystal form; and in step S3, the crystallized product is calcined to obtain an MFI-type molecular sieve catalyst.
[0030] Compared with the prior art, the preparation process of using two or more templates as mixed templates to prepare molecular sieves in the same step, the preparation process of the present application is simple, the production cost is reduced, the introduction of seed crystals can provide a starting point for the growth of the crystallized product, and the growth direction can be controlled, thereby obtaining a specific crystal form of MFI molecular sieve; the introduction of the second template and the guide agent can improve the grain morphology and pore structure of the MFI molecular sieve, thereby improving its structural stability. Moreover, the molar ratio of the second template and the guide agent includes but is not limited to the above range, and limiting it to the above range is conducive to making the grain morphology and sheet thickness of the MFI molecular sieve within the specific range of the present application, and at the same time, it is conducive to improving its pore structure, so that on the one hand, the catalytic activity of the MFI molecular sieve catalyst can be improved, the product generated by the reaction can be rapidly diffused, the occurrence of side reactions can be suppressed, and the yield of the target product can be improved. On the other hand, the generation of carbon deposits can be effectively suppressed, and the generated carbon deposits are mostly covered at the orifice of the straight-cylinder channel, which is convenient for controlling the temperature of the charcoal burning regeneration process, and suppressing the pulverization phenomenon caused by local overheating of the catalyst, thereby extending the service life of the MFI molecular sieve catalyst.
[0031] In a preferred embodiment, step S1 includes: first mixing the first silicon source and the first template to obtain a first mixed solution; dissolving the alkali in the first solvent, and then second mixing with the first mixed solution to obtain a second mixed solution; performing a first crystallization treatment on the second mixed solution to obtain a seeded system. The first mixing of the first silicon source and the first template is conducive to the first template playing a structural guiding role in the subsequent first crystallization treatment. The first mixing and the second mixing in sequence are conducive to improving the dispersibility of each raw material, and are conducive to improving the efficiency of the first crystallization treatment, and are convenient for obtaining seeds, thereby providing a starting point for the growth of the crystallized product, and are conducive to controlling the growth direction of the crystallized product, and are conducive to obtaining a specific crystal form of MFI molecular sieve.
[0032] In order to further enable the first template to play a structural guiding role in the subsequent first crystallization treatment, further improve the efficiency of the first crystallization treatment, and at the same time to improve the utilization rate of raw materials, preferably, the molar ratio of the first silicon source to the first template is (1-1.1):(0.08-0.3).
[0033] In order to make the pH and ionic strength of the reaction system within a more suitable range and further improve the efficiency of the first crystallization treatment, preferably, the weight ratio of the base to the first solvent is (0.1-0.3):(15-20).
[0034] In order to further improve the dispersibility of each raw material, thereby further improving the efficiency of the first crystallization treatment, preferably, the weight ratio of the first solvent to the first mixed liquid is (15-20):(0.5-3).
[0035] In a preferred embodiment, stirring is performed during the first mixing and the second mixing, preferably the stirring rate of the first mixing is 100-150 rpm, and the time is 20-30 min; preferably the stirring rate of the second mixing is 250-300 rpm, and the time is 60-180 min. The stirring rates and times of the first mixing and the second mixing include but are not limited to the above ranges, and limiting them within the above ranges is conducive to improving the dispersion uniformity of the above raw materials, thereby facilitating improving the efficiency of the first crystallization treatment.
[0036] In a preferred embodiment, step S2 includes: mixing the second silicon source with the second template for the third time to obtain a third mixed solution; mixing the third mixed solution with the aluminum source, the guiding agent, the second solvent and the seed for the fourth time to obtain a fourth mixed solution, and performing a second crystallization treatment on the fourth mixed solution to obtain a system containing a crystallized product. The third mixing of the second silicon source and the second template is conducive to the second template playing a structural guiding role in the subsequent second crystallization treatment. The third mixing and the fourth mixing in sequence are conducive to improving the dispersibility of each raw material, and are conducive to improving the efficiency of the second crystallization treatment, and are convenient for obtaining a crystallized product, so as to obtain a specific crystal form of the MFI molecular sieve, and at the same time, it is also conducive to adjusting the grain morphology and sheet thickness of the obtained MFI molecular sieve within an appropriate range, which is conducive to improving its pore structure, thereby helping to improve the catalytic activity, anti-coking ability and anti-pulverization ability of the MFI molecular sieve catalyst, and thus helping to extend its service life.
[0037] In order to further improve the dispersibility of each raw material, further improve the efficiency of the second crystallization treatment, further adjust the grain morphology and sheet thickness of the obtained MFI type molecular sieve within an appropriate range, further improve its pore structure, and thus further improve the performance of the MFI type molecular sieve catalyst, preferably, under stirring, the aluminum source, the directing agent, the second solvent and the seed crystal are added to the third mixed liquid in sequence.
[0038] In order to improve the stability of the framework structure of the MFI molecular sieve catalyst and further improve the purity of its crystal form, preferably, the molar ratio of the second silicon source to the aluminum source is (0.8-1.2):(0.001-0.002).
[0039] In order to further promote the second template to play a structural guiding role in the subsequent second crystallization treatment, further improve the efficiency of the second crystallization treatment, further adjust the grain morphology and sheet thickness of the obtained MFI molecular sieve within an appropriate range, further improve its pore structure, and at the same time to improve the utilization rate of raw materials, preferably, the molar ratio of the second silicon source to the second template is (0.9~1.1):(0.25~0.4).
[0040] In order to enable the seed crystals to play their role, further improve the efficiency of the second crystallization treatment, increase the growth rate of the MFI molecular sieve, and further improve its structural stability, preferably, the weight percentage of the seed crystals in the fourth mixed solution is 2-8wt%.
[0041] In a preferred embodiment, stirring is performed during the third mixing and the fourth mixing, and preferably the stirring rate of the third mixing is 400-450 rpm, and the time is 30-100 min; preferably the stirring rate of the fourth mixing is 300-400 rpm, and the time is 20-30 min. The stirring rates and times of the third mixing and the fourth mixing include but are not limited to the above ranges, and limiting them within the above ranges is conducive to improving the dispersion uniformity of the above raw materials, thereby facilitating improving the crystallization efficiency of the second crystallization treatment.
[0042] In a preferred embodiment, the first crystallization treatment includes a first heating stage and a first constant temperature stage in sequence, wherein the heating rate of the first heating stage is 2-10°C / h, the temperature of the first constant temperature stage is 95-105°C, and the time is 72-82h. The heating rate of the first heating stage in the first crystallization treatment includes but is not limited to the above range, and limiting it within the above range is conducive to uniformly increasing the temperature and inhibiting uneven grain growth caused by excessive local temperature; the temperature and time of the first constant temperature stage in the first crystallization treatment include but are not limited to the above range, and limiting it within the above range is conducive to improving the efficiency of the first crystallization treatment, and is conducive to improving the growth rate of the seed crystal, so as to facilitate obtaining the seed crystal.
[0043] In a preferred embodiment, the second crystallization treatment includes a second heating stage and a second constant temperature stage in sequence, wherein the heating rate of the second heating stage is 2 to 5°C / h, the temperature of the second constant temperature stage is 150 to 185°C, and the time is 40 to 60h. The heating rate of the second heating stage in the second crystallization treatment includes but is not limited to the above range, and limiting it within the above range is conducive to uniformly increasing the temperature, inhibiting uneven grain growth caused by excessive local temperature, and improving the uniformity of the overall morphology and size of the grains, thereby improving the performance of the prepared MFI molecular sieve catalyst; the temperature and time of the first constant temperature stage in the second crystallization treatment include but are not limited to the above range, and limiting it within the above range is conducive to improving the efficiency of the second crystallization treatment, and is conducive to improving the growth rate of the MFI molecular sieve grains, and is also conducive to regulating the grain morphology and sheet thickness of the obtained MFI molecular sieve within an appropriate range, while improving its pore structure, thereby improving the catalytic activity, anti-coking ability and anti-pulverization ability of the MFI molecular sieve catalyst, and extending its service life.
[0044] In a preferred embodiment, the first silicon source and the second silicon source independently include but are not limited to one or more of the group consisting of tetraethyl orthosilicate, silica sol, water glass, silica gel and white carbon black. Compared with other types, the use of the above-mentioned first silicon source and second silicon source is conducive to improving the catalytic activity of the MFI type molecular sieve catalyst, and is conducive to improving its grain morphology and sheet thickness.
[0045] In order to enable the first template and the second template to better play their structural guiding role, make the crystallized product grow along a specific direction, adjust the morphology and sheet thickness of the obtained MFI molecular sieve within a more suitable range and improve its pore structure, while improving the purity of the crystal form, thereby improving the catalytic activity, anti-carbon deposition ability and anti-pulverization ability of the MFI molecular sieve catalyst, preferably, the first template and the second template each independently include but are not limited to one or more of the group consisting of tetrapropylammonium hydroxide, tetrapropylammonium bromide, n-butylamine and triethylamine.
[0046] The aluminum source used in the present application can be any commonly used type in the art. In a preferred embodiment, the aluminum source includes, but is not limited to, one or more of the group consisting of aluminum nitrate, aluminum sulfate, sodium metaaluminate, and pseudo-boehmite.
[0047] In a preferred embodiment, the guiding agent includes but is not limited to one or more of the group consisting of hexadecyltrimethylammonium bromide, urea, ethylamine and ammonium nitrate. Compared with other types, the use of the above-mentioned types of guiding agents is conducive to exerting its structural guiding effect, so that the crystallized product grows along a specific direction, which is conducive to adjusting the grain morphology and sheet thickness of the obtained MFI molecular sieve within an appropriate range and improving its pore structure, thereby helping to improve the catalytic activity of the MFI molecular sieve catalyst, improve the yield of the target product, and also help to improve the MFI molecular sieve catalyst's anti-coking ability and anti-powdering ability, and extend its service life.
[0048] Ethylamine can be used as a base to adjust the pH of the system, and can also be used as a guiding agent to play a structural guiding role; the introduction of urea is conducive to improving the structural guiding effect on the MFI molecular sieve grains, and is conducive to regulating the thickness of its lamellae within a suitable range. In a preferred embodiment, the guiding agent is a combination of ethylamine and urea, and the molar ratio of ethylamine to urea is (0.02-1): (0.12-2). The molar ratio of ethylamine to urea includes but is not limited to the above range. Limiting it to the above range is conducive to improving the structural guiding effect of the guiding agent, thereby helping to adjust the grain morphology and lamella thickness of the obtained MFI molecular sieve within a suitable range and improve its pore structure, thereby helping to improve the above performance of the MFI molecular sieve catalyst.
[0049] In order to adjust the pH and ionic strength of the system within a more suitable range, thereby further improving the performance of the prepared MFI molecular sieve catalyst, preferably, the base includes but is not limited to one or more of the group consisting of sodium hydroxide, sodium carbonate, potassium hydroxide and sodium bicarbonate.
[0050] In order to improve the dispersibility of each raw material, preferably, the first solvent and the second solvent each independently include but are not limited to one or more selected from the group consisting of water, ethanol and methanol.
[0051] In a preferred embodiment, step S1 further comprises: sequentially performing a first solid-liquid separation and a first drying on the seed crystal-containing system to obtain seed crystals. Performing a first solid-liquid separation and a first drying on the seed crystal-containing system is beneficial to removing the solvent component in the seed crystal-containing system.
[0052] In order to further remove the solvent component in the seed crystal system and reduce the solvent content in the crystals, preferably, the first drying temperature is 60 to 140° C. and the time is 8 to 24 hours.
[0053] In a preferred embodiment, in step S3, the calcination temperature is 400-600°C and the time is 4-10 hours. The calcination temperature and time in step S3 include but are not limited to the above ranges, and limiting them within the above ranges is conducive to improving the structural stability of the prepared MFI type molecular sieve catalyst, thereby extending its service life, and is also conducive to increasing its specific surface area, thereby facilitating improving the catalytic activity of the MFI type molecular sieve catalyst.
[0054] In a preferred embodiment, between step S2 and step S3, it also includes: sequentially performing a second solid-liquid separation and a second drying on the crystallization product system, preferably the temperature of the second drying is 80 to 120°C, and the time is 4 to 10 hours. Performing a second solid-liquid separation and a second drying on the crystallization product system, and the temperature and time of the second drying include but are not limited to the above ranges, and limiting it within the above range is conducive to removing the solvent component in the crystallization product system to obtain a crystallized product, which is convenient for subsequent roasting and is conducive to suppressing the splashing of the solvent component during the roasting process.
[0055] The third aspect of the present application also provides an application of the above-mentioned MFI type molecular sieve catalyst in the methanol to propylene reaction.
[0056] The MFI molecular sieve catalyst in the present application is a sheet structure, and has a relatively short straight-tube channel in the thickness direction. On the one hand, the catalytic activity of the MFI molecular sieve catalyst can be improved, and the generated product can be diffused quickly, thereby suppressing the occurrence of side reactions and improving the yield of the target product. On the other hand, it can also effectively suppress the formation of carbon deposits, and the generated carbon deposits are mostly covered at the orifices of the straight-tube channel, which is convenient for controlling the temperature of the charcoal burning regeneration process and suppressing the pulverization phenomenon caused by local overheating of the catalyst, thereby extending the service life of the MFI molecular sieve catalyst. The above-mentioned MFI molecular sieve catalyst is applied in the reaction of methanol to propylene (MTP), which can improve the yield of propylene and reduce the pressure drop of the final reactor.
[0057] The present application is further described in detail below in conjunction with specific embodiments. These embodiments should not be construed as limiting the scope of protection claimed in the present application.
[0058] Example 1
[0059] A method for preparing an MFI type molecular sieve catalyst comprises the following steps:
[0060] (1) 174 g of tetraethyl orthosilicate (silicon source) was weighed and stirred at 300 rpm for 20 min, and then 68 g of tetrapropylammonium hydroxide aqueous solution (TPAOH, template, weight concentration of 25 wt%) was added thereto, and the mixture was stirred at 150 rpm for 20 min to coagulate the solution to obtain a mixed solution;
[0061] (2) 55 g of NaOH was dissolved in 270 g of water, and after it was fully dissolved, it was added dropwise to the mixed solution obtained in step (1), and stirred at a rate of 300 rpm for 180 min to obtain a colloidal liquid. The obtained colloidal liquid was transferred to a polytetrafluoroethylene reactor, heated to 100° C. at a rate of 10° C. / h, and allowed to stand for crystallization for 75 h to obtain a seed crystal system;
[0062] (3) filtering and washing the seed crystal system in turn to separate the solid and liquid, and drying the obtained solid in an oven at 120° C. for 20 h to obtain seed crystals;
[0063] (4) 167 g of silica sol (weight concentration of 30 wt%) (silicon source) and 203 g of TPAOH (template, weight concentration of 25 wt%) were weighed, stirred at 400 rpm for 30 min, and then 3 g of aluminum sulfate (aluminum source) was added thereto, and stirred at 400 rpm for 60 min to obtain a mixed solution;
[0064] (5) 2.5 g of ethylamine was dissolved in 23 g of water, and after it was fully dissolved, it was added dropwise to the mixed solution obtained in step (4), and stirred at a rate of 300 rpm for 180 min, 6 g of urea (directing agent) was added thereto, and stirring was continued for 30 min. 3 g of the seed crystals obtained in step (4) were added, and stirring was continued for 30 min. All of them were transferred to a polytetrafluoroethylene reactor, and the temperature was increased to 150° C. at a rate of 5° C. / h, and the mixture was allowed to stand for crystallization for 60 h to obtain a system containing a crystallized product;
[0065] (6) The system containing the crystallized product was filtered and washed in sequence, and the obtained solid was placed in an oven at 120° C. and dried for 10 h to obtain a crystallized product. The crystallized product was transferred to a tubular furnace and calcined at 550° C. for 10 h to obtain an MFI type molecular sieve catalyst.
[0066] The XRD pattern of the MFI type molecular sieve catalyst prepared in Example 1 is as follows: Figure 1 As shown. Figure 1 It can be seen that the diffraction peaks of the MFI type molecular sieve catalyst are consistent with the characteristic peaks of the ZSM-5 molecular sieve, and there are no impurity peaks, indicating that its crystal purity is high.
[0067] The scanning electron microscope image of the MFI type molecular sieve catalyst prepared in Example 1 is as follows: Figure 2 As shown. Figure 2 It can be seen that the MFI molecular sieve catalyst prepared in Example 1 is a flaky structure with a thickness of 139 to 142 nm. The shape of the cross section perpendicular to the thickness direction is a hexagon. The hexagon includes two parallel sides, and the direction of the side is the y direction. The vertical distance between the two is 229.7 nm, the maximum value along the y direction is 423.2 to 506.8 nm, and the ratio of the maximum value along the y direction to the length of the side is (1.6 to 2):1.
[0068] Example 2
[0069] The difference from Example 1 is that the ratio of the molar number of TPAOH (template) in step (4) to the total molar number of ethylamine and urea (directing agent) in step (5) is 0.2:0.8, and the remaining steps are the same as Example 1.
[0070] Example 3
[0071] The difference from Example 1 is that the ratio of the molar number of TPAOH (template) in step (4) to the total molar number of ethylamine and urea (directing agent) in step (5) is 0.5:0.1, and the remaining steps are the same as Example 1.
[0072] Example 4
[0073] The difference from Example 1 is that in step (1), the molar ratio of tetraethyl orthosilicate (silicon source) to TPAOH (template) is 1.1:0.08, and the remaining steps are the same as Example 1.
[0074] Example 5
[0075] The difference from Example 1 is that in step (1), the molar ratio of tetraethyl orthosilicate (silicon source) to TPAOH (template) is 1:0.3, and the remaining steps are the same as Example 1.
[0076] Example 6
[0077] The difference from Example 1 is that in step (1), the molar ratio of tetraethyl orthosilicate (silicon source) to TPAOH (template) is 0.8:0.5, and the remaining steps are the same as Example 1.
[0078] Example 7
[0079] The difference from Example 1 is that in step (4), the molar ratio of silica sol (silicon source), TPAOH (template) and aluminum sulfate (aluminum source) is 0.9:0.25:0.001, and the remaining steps are the same as Example 1.
[0080] Example 8
[0081] The difference from Example 1 is that in step (4), the molar ratio of silica sol (silicon source), TPAOH (template) and aluminum sulfate (aluminum source) is 1.1:0.4:0.002, and the remaining steps are the same as Example 1.
[0082] Example 9
[0083] The difference from Example 1 is that in step (4), the molar ratio of silica sol (silicon source), TPAOH (template) and aluminum sulfate (aluminum source) is 0.6:0.5:0.004, and the remaining steps are the same as Example 1.
[0084] Example 10
[0085] The difference from Implementation 1 is that in step (5), the weight percentage of the seed crystal is 2wt%, and the remaining steps are the same as Implementation 1.
[0086] Embodiment 11
[0087] The difference from Example 1 is that in step (5), the weight percentage of the seed crystal is 8wt%, and the remaining steps are the same as Example 1.
[0088] Example 12
[0089] The difference from Example 1 is that in step (5), the weight percentage of the seed crystal is 0.7wt%, and the remaining steps are the same as Example 1.
[0090] Embodiment 13
[0091] The difference from Example 1 is that in step (2), the temperature is raised to 95° C. at a rate of 2° C. / h and allowed to stand for crystallization for 82 h to obtain a seed crystal system. The remaining steps are the same as in Example 1.
[0092] Embodiment 14
[0093] The difference from Example 1 is that in step (2), the temperature is raised to 105° C. at a rate of 10° C. / h and allowed to stand for crystallization for 72 h to obtain a seed crystal system. The remaining steps are the same as in Example 1.
[0094] Embodiment 15
[0095] The difference from Example 1 is that in step (2), the temperature is raised to 120° C. at a rate of 15° C. / h, and the mixture is allowed to stand for crystallization for 65 h to obtain a seed crystal system. The remaining steps are the same as in Example 1.
[0096] Example 16
[0097] The difference from Example 1 is that in step (5), the temperature is raised to 170°C at a rate of 2°C / h, and the mixture is allowed to stand for crystallization for 60 hours to obtain a system containing a crystallized product. The remaining steps are the same as in Example 1.
[0098] Embodiment 17
[0099] The difference from Example 1 is that in step (5), the temperature is raised to 185°C at a rate of 5°C / h, and the mixture is allowed to stand for crystallization for 40 hours to obtain a system containing a crystallized product. The remaining steps are the same as in Example 1.
[0100] Embodiment 18
[0101] The difference from Example 1 is that in step (5), the temperature is raised to 130°C at a rate of 10°C / h, and the mixture is allowed to stand for crystallization for 30 hours to obtain a system containing a crystallized product. The remaining steps are the same as in Example 1.
[0102] Embodiment 19
[0103] The difference from Example 1 is that in step (6), the calcination temperature is 400° C. and the calcination time is 4 h. The remaining steps are the same as Example 1.
[0104] Embodiment 20
[0105] The difference from Example 1 is that in step (6), the calcination temperature is 350° C. and the calcination time is 3 h. The remaining steps are the same as Example 1.
[0106] Comparative Example 1
[0107] A commercially available small-grain ZSM-5 molecular sieve catalyst, the specific surface area of the ZSM-5 molecular sieve catalyst is 324.8 cm 2 / g, and the average pore size is 3.8127nm.
[0108] The scanning electron microscope image of the commercially available small-grain ZSM-5 molecular sieve catalyst in Comparative Example 1 is as follows: Figure 3 As shown by Figure 3 It can be seen that the small-grain ZSM-5 molecular sieve catalyst in Comparative Example 1 has a morphology of small spherical grains, and the particle size thereof is less than 200 nm.
[0109] Compared with Example 1, the small-grain ZSM-5 molecular sieve catalyst in Comparative Example 1 has smaller grains, which is difficult to filter and wash and not easy to recover. Not only is it easy to cause catalyst loss, but multiple washings will also increase the amount of wastewater, resulting in higher production costs.
[0110] Comparative Example 2
[0111] The difference from Example 1 is that the ratio of the molar number of TPAOH (template) in step (4) to the total molar number of ethylamine and urea (directing agent) in step (5) is 0.1:0.8, and the remaining steps are the same as Example 1.
[0112] The following tests were performed on the MFI molecular sieve catalysts prepared in Examples 1 to 20 of the present application and Comparative Example 2 and the commercially available small-grain ZSM-5 molecular sieve catalyst in Comparative Example 1: (1) the average pore size was measured by nitrogen adsorption method; (2) the specific surface area was measured according to the method in GB / T19587-2017; (3) the pore volume was measured according to the method in ASTM D6761-17 "Standard Test Method for Determination of the Total Pore Volume of Catalysts and Catalyst Carriers"; (4) the crushing rate of the MFI molecular sieve catalyst was measured by screening out ≤10 mesh; (5) the longest single cycle life was measured according to the method in HG / T 5190-2017.
[0113] The test results are shown in Table 1 below.
[0114] Table 1
[0115]
[0116]
[0117] Under the same conditions, the mass ratio of water to methanol is 0.7:1, and the space velocity of methanol is 1h -1The MFI molecular sieve catalysts prepared in Examples 1 to 20 of the present application and Comparative Example 2 and the commercially available small-grain ZSM-5 molecular sieve catalyst in Comparative Example 1 were used as catalysts to catalyze the methanol to propylene (MTP) reaction at 480° C. and normal pressure, and the final reactor pressure drop was obtained based on the reactor pressure gauge reading. The specific test results are shown in Table 2 below.
[0118] Table 2
[0119]
[0120]
[0121] From the above description, it can be seen that the above embodiments of the present invention achieve the following technical effects:
[0122] Compared with the ZSM-5 molecular sieve in Comparative Example 1, the MFI molecular sieve prepared in Example 1 has a longer single-cycle life and a higher yield of propylene produced by catalyzing the MTP reaction than that in Comparative Example 1. It can be seen that the MFI molecular sieve catalyst in the present application can adjust the length of the straight-cylindrical channel by adjusting the thickness of the sheet structure while maintaining the overall grain morphology and size of the molecular sieve, so that it can better adapt to the methanol to propylene (MTP reaction). The thickness of the MFI molecular sieve catalyst and the cross-sectional shape and size of the straight-cylindrical channel include but are not limited to the above ranges. By limiting it to the above range, on the one hand, the catalytic activity of the MFI molecular sieve catalyst can be improved, the generated product can be rapidly diffused, the occurrence of side reactions can be suppressed, and the yield of the target product can be improved. On the other hand, the formation of carbon deposits can be effectively suppressed, and the generated carbon deposits are mostly covered at the orifices of the straight-cylindrical channels, which is convenient for controlling the temperature of the carbonization regeneration process and suppressing the pulverization phenomenon caused by local overheating of the catalyst, thereby extending the service life of the MFI molecular sieve catalyst.
[0123] The longest single cycle life and the yield of propylene produced by catalytic MTP reaction of Comparative Example 2 are lower than those of Examples 1 to 3. It can be seen that the molar ratio of the second template agent to the directing agent includes but is not limited to the above range. Limiting it within the above range is beneficial to improving its pore structure, thereby on the one hand improving the catalytic activity of the MFI molecular sieve catalyst, enabling the products generated by the reaction to diffuse rapidly, inhibiting the occurrence of side reactions, and improving the yield of the target product; on the other hand, it can effectively inhibit the formation of carbon deposits, and the generated carbon deposits are mostly covered at the orifices of the straight-cylindrical pores, which is convenient for controlling the temperature of the carbonization regeneration process and inhibiting the pulverization phenomenon caused by local overheating of the catalyst, thereby extending the service life of the MFI molecular sieve catalyst.
[0124] By comparing Examples 1, 4 to 6, it can be seen that, compared with other ranges, limiting the molar ratio of the first silicon source to the first template within the above range is beneficial to enabling the first template to play a structural guiding role in the subsequent first crystallization treatment, which is beneficial to improving the efficiency of the first crystallization treatment and at the same time beneficial to improving the utilization rate of raw materials.
[0125] By comparing Examples 1, 7 to 9, it can be seen that the molar ratio of the second silicon source to the second template includes but is not limited to the above range. Limiting it within the above range is conducive to enabling the second template to play a structural guiding role in the subsequent second crystallization treatment, thereby facilitating the adjustment of the grain morphology and sheet thickness of the obtained MFI type molecular sieve within an appropriate range, thereby facilitating the improvement of its pore structure; the molar ratio of the second silicon source to the aluminum source includes but is not limited to the above range. Limiting it within the above range is conducive to improving the stability of the skeleton structure of the MFI type molecular sieve catalyst, thereby facilitating the improvement of the purity of its crystal form.
[0126] By comparing Examples 1 and 10 to 12, it can be seen that, compared with other ranges, limiting the weight percentage of the seed crystals within the above range is beneficial to enabling the seed crystals to play their role, and is beneficial to improving the efficiency of the second crystallization treatment, thereby helping to increase the growth rate of the MFI type molecular sieve, and further helping to improve its pore structure and structural stability.
[0127] By comparing Examples 1 and 13 to 15, it can be seen that the various process parameters (heating rate, temperature and time) of the first crystallization treatment include but are not limited to the above-mentioned ranges. Limiting them within the above-mentioned ranges is conducive to uniformly increasing the temperature, inhibiting uneven grain growth caused by local excessive temperature, and improving the efficiency of the first crystallization treatment, thereby helping to increase the growth rate of the seed crystal and facilitate obtaining the seed crystal.
[0128] By comparing Examples 1 and 16 to 18, it can be seen that the process parameters of the second crystallization treatment (heating rate, temperature and time) include but are not limited to the above-mentioned ranges. Limiting them within the above-mentioned ranges is beneficial to uniformly increase the temperature, inhibiting uneven grain growth caused by excessive local temperature, improving the uniformity of the overall morphology and size of the grains, and increasing the growth rate of the MFI molecular sieve grains. It is also beneficial to improve its pore structure, thereby improving the catalytic activity, anti-carbon deposition ability and anti-pulverization ability of the MFI type molecular sieve catalyst and extending its service life.
[0129] Comparing Examples 1, 19 and 20, Example 20 has an incompletely developed pore structure of the MFI type zeolite catalyst due to its lower calcination temperature, resulting in a relatively small average pore size. It can be seen that, compared with other ranges, limiting the calcination temperature and time within the above range is beneficial to improving the structural stability of the prepared MFI type zeolite catalyst, thereby helping to extend its service life, and is also beneficial to increasing its specific surface area, thereby helping to improve the catalytic activity of the MFI type zeolite catalyst.
[0130] It should be noted that the terms "first", "second", etc. in the specification and claims of the present application are used to distinguish similar objects, and are not necessarily used to describe a specific order or sequence. It should be understood that the terms used in this way can be interchangeable where appropriate, so that the embodiments of the present application described herein can be implemented in an order other than those described herein, for example.
[0131] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. An MFI type molecular sieve catalyst, characterized in that: The MFI molecular sieve catalyst is a sheet structure, having a straight-cylindrical channel structure in the thickness direction and a Z-shaped channel structure in the plane direction; the cross-sectional shape of the straight-cylindrical channel is elliptical, the length of its major axis is 0.57-0.58 nm, and the length of its minor axis is 0.51-0.52 nm; the thickness of the MFI molecular sieve catalyst is 90-200 nm.
2. The MFI molecular sieve catalyst according to claim 1, characterized in that The plane of the MFI molecular sieve catalyst includes an x direction and a y direction which are perpendicular to each other, the maximum value along the x direction is 200 to 400 nm, and the maximum value along the y direction is 400 to 700 nm; Preferably, in the MFI type molecular sieve catalyst, the shape of the cross section perpendicular to the thickness direction is a hexagon, the hexagon includes two parallel sides, and the direction of the side is the y direction, preferably the vertical distance between the two is 200 to 400 nm, and preferably the ratio of the maximum value along the y direction to the length of the side is (1.4 to 2.3):
1.
3. The MFI type molecular sieve catalyst according to claim 1, characterized in that: The pore volume of the MFI molecular sieve catalyst is 0.17 to 0.23 cm 3 / g, with a specific surface area of 330-375cm 2 / g.
4. A method for preparing the MFI molecular sieve catalyst according to any one of claims 1 to 3, characterized in that: The preparation method of the MFI type molecular sieve catalyst comprises: Step S1, performing a first crystallization treatment on a first silicon source, a first template, a base and a first solvent to obtain a seed crystal system; Step S2, performing a second crystallization treatment on the second silicon source, the aluminum source, the second template, the directing agent, the second solvent and the seed crystal to obtain a system containing a crystallized product; the molar ratio of the second template to the directing agent is (0.2 to 0.5): (0.1~0.8); Step S3, calcining the crystallized product to obtain the MFI type molecular sieve catalyst.
5. The method for preparing the MFI type molecular sieve catalyst according to claim 4, characterized in that: The step S1 comprises: performing a first mixing of the first silicon source and the first template to obtain a first mixed solution; dissolving the alkali in the first solvent and then performing a second mixing with the first mixed solution to obtain a second mixed solution; performing the first crystallization treatment on the second mixed solution to obtain the seed-containing system; Preferably, the molar ratio of the first silicon source to the first template is (1-1.1):(0.08-0.3); Preferably, the weight ratio of the base to the first solvent is (0.1-0.3):(15-20); Preferably, the weight ratio of the first solvent to the first mixed solution is (15-20):(0.5-3); Preferably, stirring is performed during the first mixing and the second mixing. Preferably, the stirring rate of the first mixing is 100-150 rpm and the time is 20-30 min. Preferably, the stirring rate of the second mixing is 250-300 rpm and the time is 60-180 min.
6. The method for preparing the MFI type molecular sieve catalyst according to claim 4, characterized in that: The step S2 comprises: performing a third mixing of the second silicon source and the second template to obtain a third mixed solution; performing a fourth mixing of the third mixed solution with the aluminum source, the directing agent, the second solvent and the seed crystal to obtain a fourth mixed solution, and performing the second crystallization treatment on the fourth mixed solution to obtain the crystallization product-containing system; Preferably, the molar ratio of the second silicon source to the aluminum source is (0.8-1.2):(0.001-0.002); Preferably, the molar ratio of the second silicon source to the second template is (0.9-1.1):(0.25-0.4); Preferably, the weight percentage of the seed crystals in the fourth mixed solution is 2-8wt%; Preferably, stirring is performed during the third mixing and the fourth mixing. Preferably, the stirring rate of the third mixing is 400-450 rpm and the time is 30-100 min. Preferably, the stirring rate of the fourth mixing is 300-400 rpm and the time is 20-30 min.
7. The method for preparing the MFI type molecular sieve catalyst according to any one of claims 4 to 6, characterized in that: The first crystallization treatment includes a first temperature rise stage and a first constant temperature stage in sequence, wherein the temperature rise rate of the first temperature rise stage is 2-10°C / h, the temperature of the first constant temperature stage is 95-105°C, and the time is 72-82h; Preferably, the second crystallization treatment includes a second heating stage and a second constant temperature stage in sequence, wherein the heating rate of the second heating stage is 2-5°C / h, the temperature of the second constant temperature stage is 150-185°C, and the time is 40-60h.
8. The method for preparing the MFI type molecular sieve catalyst according to any one of claims 4 to 6, characterized in that: The first silicon source and the second silicon source are each independently selected from one or more of the group consisting of tetraethyl orthosilicate, silica sol, water glass, silica gel and white carbon black; Preferably, the first template and the second template are each independently selected from one or more of the group consisting of tetrapropylammonium hydroxide, tetrapropylammonium bromide, n-butylamine and triethylamine; Preferably, the aluminum source is selected from one or more of the group consisting of aluminum nitrate, aluminum sulfate, sodium metaaluminate and pseudo-boehmite; Preferably, the directing agent is selected from one or more of the group consisting of hexadecyltrimethylammonium bromide, urea, ethylamine and ammonium nitrate; preferably, the directing agent is a combination of the ethylamine and the urea, and the molar ratio of the ethylamine to the urea is (0.02-1):(0.12-2); Preferably, the base is selected from one or more of the group consisting of ethylamine, sodium hydroxide, sodium carbonate, potassium hydroxide and sodium bicarbonate; Preferably, the first solvent and the second solvent are each independently selected from one or more of the group consisting of water, ethanol and methanol.
9. The method for preparing the MFI type molecular sieve catalyst according to claim 4, characterized in that: The step S1 further comprises: sequentially performing a first solid-liquid separation and a first drying on the seed crystal-containing system to obtain the seed crystal; Preferably, the first drying temperature is 60 to 140° C. and the time is 8 to 24 hours; Preferably, in step S3, the calcination temperature is 400-600° C. and the calcination time is 4-10 h; Preferably, between step S2 and step S3, the process further includes: sequentially performing a second solid-liquid separation and a second drying on the crystallized product system, and more preferably, the second drying is performed at a temperature of 80 to 120° C. for a time of 4 to 10 hours.
10. Use of the MFI molecular sieve catalyst according to any one of claims 1 to 3 in a methanol to propylene reaction.